FISIOTERAPIA DESPORTIVA: UM ESPAÇO PARA A VIVÊNCIA ACADÊMICA NO FUTSAL - Bigolin, Simone E.; Schumann, Daniel; Machado, Guilherme F.; Schumacher, Patrícia H.; Vargas, Priscila (Salão do Conhecimento, 2013)
Resumo